2014
DOI: 10.4136/ambi-agua.1340
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of cadmium in vegetable sponge (Luffa cylindrica)

Abstract: The use of biomass as an adsorbent material follows the principles of sustainability and Green Chemistry. Given the low cost, high abundance, easy availability and high adsorption capacity of the vegetable sponge (Luffa cylindrica), this study aimed to explore the adsorption process of the toxic metal cadmium (Cd). The parameters evaluated were pH, contact time, adsorption isotherms, thermodynamic parameters, percolation and desorption. The proposed method showed high retention of Cd ions, being 99.80% at pH 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Several researchers have reported adsorption using LAC to be effective in heavy metals removal from industrial effluents; thus, the removal of Pb 2+ in water, removal of divalent metals, methylene blue dye, cyanide ions, cadmium ions, common laboratory dye and adsorption of brilliant green from aqueous solutions have been reported by Adewuyi and Pereira (2017), Oboh et al (2011), Demir et al (2008), Arana et al (2017), Lindino et al (2014), Calciedo et al (2018 and Segun et al (2014). Furthermore, Nwosu-obieogu et al (2021) reported iron (II) adsorption from textile wastewater using LAC.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported adsorption using LAC to be effective in heavy metals removal from industrial effluents; thus, the removal of Pb 2+ in water, removal of divalent metals, methylene blue dye, cyanide ions, cadmium ions, common laboratory dye and adsorption of brilliant green from aqueous solutions have been reported by Adewuyi and Pereira (2017), Oboh et al (2011), Demir et al (2008), Arana et al (2017), Lindino et al (2014), Calciedo et al (2018 and Segun et al (2014). Furthermore, Nwosu-obieogu et al (2021) reported iron (II) adsorption from textile wastewater using LAC.…”
Section: Introductionmentioning
confidence: 99%
“…Oboh (2018) reported on the physical properties of luffa cylindrica bisorbent, the specific surface area (BET (m 2 /g), total surface area (m 2 /g), pore diameter range and bulk density (g/cm 3 ) were determined as 0.28, 1.1895, 1051.309204 to 0.003577, and 0.34, respectively, it signified that the surface area is low, with pore diameter and bulk density values in concordance with those found in typical mesoporous materials. A few researchers have reported the use of luffa cylindrica as an adsorbent in removing heavy metal, the removal of Pb 2+ in water (Adewuyi & Pereira, 2017), removal of divalent metals (Oboh, Aluyor, & Audu, 2011), methylene blue dye (Demir, Top, Balko¨se, & lku, 2008), cyanide ions (Arana, González, Navarrete, & Caicedo, 2017), nickel ions (Oboh, 2018), cadmium ions (Lindino, Marciniak, Gonçalves, & Strey, 2014), common laboratory dyes (Caicedo et al, 2018), and adsorption of brilliant green (Segun Esan et al., 2014) from aqueous solutions. Hence, this study presents the use of luffa cylindrica as a potential, environmentally friendly, and low‐cost adsorbent for the remediation of Cr (VI) from textile wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of the application of biomass in the adsorption of heavy metals can be found in lead and copper adsorption of pine cone at pH 5.0 (Awad and Erkurt, 2014), in lead removal by pine bark (Montes-Atenas and Schroeder, 2015; Cutillas-Barreiro et al , 2014), or using kelps (Feng and Aldrich, 2004) and vegetable sponge (Lindino et al , 2014).…”
Section: Introductionmentioning
confidence: 99%